ENT 600 : Grant proposal : Innovious Tech / Nur Atikah Nordin … [et al.] - Nordin, Nur Atikah; Abd Jalil, Noor Amira; Usari, Farah Farena; Idris, Norliyana Syazwani; Karim, Nurul Zatil Athirah (2017)
The team is to invent a new type of wheelbarrow known as the 'Next Barrow'. The product is a rechargeable wheelbarrow that can be operated using function buttons to simplify the job of the users.